2005
DOI: 10.1016/j.orthres.2005.02.016.1100230625
|View full text |Cite
|
Sign up to set email alerts
|

Proposed model of botulinum toxin-induced muscle weakness in the rabbit

Abstract: Osteoarthritic patients show only a weak association between radiographic signs of joint disease and joint pain and disability. Conversely, muscle weakness is one of the earliest and most common symptoms of patients with osteoarthritis (OA). However, while many experimental models of osteoarthritis include a component of muscular weakness, no model has isolated this factor satisfactorily. Therefore, the purpose of this study was to develop and validate an experimental animal model of muscle weakness for future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…Our experiments have several implications for clinicians. One of the major effects of local BoNT‐A injection was local muscle weakness and muscle atrophy 37. In cosmetic applications, the atrophy effect of BoNT‐A injection is used for gastrocnemius muscle toning 38.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments have several implications for clinicians. One of the major effects of local BoNT‐A injection was local muscle weakness and muscle atrophy 37. In cosmetic applications, the atrophy effect of BoNT‐A injection is used for gastrocnemius muscle toning 38.…”
Section: Discussionmentioning
confidence: 99%
“…Longino et al (2005) found that in rabbits with BTX injected to the quadriceps (35 U/100 g), peak vertical GRFs were up to 50% lower in BTX-injected rabbits than controls six months post-injection. However, to our knowledge, weight-bearing activity has never been quantified in rodents after BTX injection.…”
Section: Introductionmentioning
confidence: 93%
“…Each half was subdivided into medial, central and lateral section. One sixth of the total botox dose was injected into each section to increase botox diffusion and to inject directly into the vastus lateralis, rectus femoris and vastus medialis muscles (Longino et al, 2005b;Yaraskavitch et al, 2008).…”
Section: Botulinum Type a Toxin: Injection Protocolmentioning
confidence: 99%